2013
DOI: 10.1080/11250003.2012.697925
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of the rough rayRaja radula(Chondrichthyes: Rajidae) from the Gulf of Gabès (central Mediterranean Sea)

Abstract: The food habits of rough ray Raja radula were investigated, with respect to sex, size and season, based on stomach content analyses of specimens collected from commercial fisheries, monthly during 2007 in the Gulf of Gabès (Central Mediterranean Sea). Of 950 stomachs examined, 183 were empty (19.26%). The overall diet of R. radula mainly consisted of crustacean decapods, teleosts and molluscs. Polycheates, sipunculids and echinoderms were minor dietary components. No differences were observed in the major prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Maximum total length observed in our study for R. clavata (54.5 cm) were slightly smaller than found in a study carried out (73.2 cm) in the Southeastern Black Sea (Demirhan et al, 2005). Kadri et al (2013) reported that the TL of R. radula collected from the Gulf of Gabes (southern Tunisia, central Mediterranean Sea) ranged from 13.4 to 65 cm, similar to our report (51.5 to 56.5 cm). The average total length and weight of T. marmorata collected from North-Eastern Mediterranean were detected to be between 12.26 to 40 cm, 40.40 to 1062.00 g, respectively by Duman and Basusta (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Maximum total length observed in our study for R. clavata (54.5 cm) were slightly smaller than found in a study carried out (73.2 cm) in the Southeastern Black Sea (Demirhan et al, 2005). Kadri et al (2013) reported that the TL of R. radula collected from the Gulf of Gabes (southern Tunisia, central Mediterranean Sea) ranged from 13.4 to 65 cm, similar to our report (51.5 to 56.5 cm). The average total length and weight of T. marmorata collected from North-Eastern Mediterranean were detected to be between 12.26 to 40 cm, 40.40 to 1062.00 g, respectively by Duman and Basusta (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Delpiani, Spath, & Figueroa, 2013; Lipej, Mavrič, Paliska, & Capapé, 2013; Orlov, 1998), which may be due to sexual dimorphism, spatiotemporal segregation and increased energetic requirements during gestation (Delpiani et al., 2013). Many rays showed seasonal and/or regional variation in diet, which has been hypothesized to be related to changes in prey availability, abundance and distribution (Barbini & Lucifora, 2011; Bornatowski, Robert, & Costa, 2010; Braccini & Perez, 2005; Kadri, Saïdi, Marouani, Bradai, & Bouaïn, 2013; Molina & Cazorla, 2015; Saglam, Ak, Kutlu, & Aydin, 2010; Saglam & Bascinar, 2008; San Martin, Braccini, Tamini, Chiaramonte, & Perez, 2007; Szczepanski & Bengtson, 2014), but could also be related to ray seasonal migrations influenced by environmental variables (Schlaff, Heupel, & Simpendorfer, 2014). Ontogenetic shifts in ray diets are widespread, where larger prey items were consumed with increasing body size (e.g.…”
Section: Predator–prey Interactionsmentioning
confidence: 99%